In praise of Prambanan; Dutch essays on the Loro Jonggrang temple complex - Jordaan, Roy E. (Translation Series, 1996)
In praise of Prambanan is devoted to the Hindu-Javanese temple complex of Candi Prambanan, also known by its locally more popular name of Candi Loro Jonggrang. The book has two parts. Part One is a general introduction to the temple complex based on an examination of the existing scholarly literature. It offers a detailed state-of-the-art survey of publications on Candi Prambanan as well as of the religious conditions which made its creation possible. Part Two contains a selection of important articles - in English translation - about the temple complex by prominent Dutch scholars all of whom had first-hand knowledge of it: J.W. IJzerman, J.Ph. Vogel, N.J. Krom, F.D.K. Bosch, B. de Haan, W.F. Stutterheim, V.R. van Romondt and A.J. Bernet Kempers. The book is richly illustrated with photographs, drawings and maps. Roy E. Jordaan, currently a private scholar, obtained his PhD in anthropology from Leiden University.